Strained Compromises? Danish Flexicurity During Crisis - Ibsen, Christian Lyhne (Nordic Journal of Working Life Studies, 2011)
The Danish concept of flexicurity in a `Golden Triangle´ of low job protection, high income security and high employment security is not only about a balance between labor market flexibility and social security. Arguably, it is also a series of more or less stable underlying compromises between social partners about the main mechanisms and aims of labor market regulation which - supposedly - should be focused on employment rather than jobs, and competition on quality rather than on labor costs. However, the `Golden Triangle´ - this article argues - seems in need of complementary concepts. The article therefore introduces, `centralized decentralization´ - a concept that directs our attention to forms of flexibility and security primarily for people in work. Most studies on Danish flexicurity have been carried out under favorable economic conditions. In light of the economic slump hitting Denmark in 2008, this article investigates if and how the recession challenged these compromises by comparing two rounds of case-based interviews in three metalworking companies in 2007 and 2009. It is shown that practice has indeed changed - albeit modestly - due to worsened economic circumstances. For example the case studies show that the hypothesized preference for external numerical flexibility is perhaps too crude as employers use different ways to restructure employment. Especially the examples of de facto concessionary bargaining to save jobs are important here - although the extent of concessions is modest. The evidence thus suggests that the `Golden Triangle´ flexicurity compromises are indeed strained by the economic cycle and that responses to impetus for restructuring are far more nuanced than sometimes portrayed. It is argues that more company studies across national labor markets and industrial relations institutions will enhance our understanding of the dynamics during times of restructuring.